A single resistance exercise session improves myocardial contractility in spontaneously hypertensive rats - Fernandes,A.A. (2015)
Resistance training evokes myocardial adaptation; however, the effects of a single resistance exercise session on cardiac performance are poorly understood or investigated. This study aimed to investigate the effects of a single resistance exercise session on the myocardial contractility of spontaneously hypertensive rats (SHRs). Male 3-month-old SHRs were divided into two groups: control (Ct) and exercise (Ex). Control animals were submitted to sham exercise. Blood pressure was measured in conscious rats before the exercise session to confirm the presence of arterial hypertension. Ten minutes after the exercise session, the animals were anesthetized and killed, and the hearts were removed. Cardiac contractility was evaluated in the whole heart by the Langendorff technique and by isometric contractions of isolated left ventricular papillary muscles. SERCA2a, phospholamban (PLB), and phosphorylated PLB expression were investigated by Western blot. Exercise increased force development of isolated papillary muscles (Ex=1.0±0.1 g/mg vs Ct=0.63±0.2 g/mg, P<0.05). Post-rest contraction was greater in the exercised animals (Ex=4.1±0.4% vs Ct=1.7±0.2%, P<0.05). Papillary muscles of exercised animals developed greater force under increasing isoproterenol concentrations (P<0.05). In the isolated heart, exercise increased left ventricular isovolumetric systolic pressure (LVISP; Δ +39 mmHg; P<0.05) from baseline conditions. Hearts from the exercised rats presented a greater response to increasing diastolic pressure. Positive inotropic intervention to calcium and isoproterenol resulted in greater LVISP in exercised animals (P<0.05). The results demonstrated that a single resistance exercise session improved myocardial contractility in SHRs.